The role of fintech and sustainable practices on financial reporting quality in Jordanian customs clearance companies - Qahman, Ashraf Ibrahim Abdallah; Madi, Aziz; Shubailat, Omar M; Al-Zaqeba, Murad Ali Ahmad; AlOqaily, Ahmed Nader (International Journal of Innovative Research and Scientific Studies, 2025)
This paper examines the effect of FinTech adoption and sustainable practices on financial reporting quality in Jordanian customs clearance companies. It also investigates the moderating roles of regulatory compliance and the culture of innovation. This study used quantitative research to collect data from Jordanian customs clearance companies. Structured questionnaires were used to gather data from employees and management personnel involved in financial reporting. The survey was conducted for three weeks, achieving 142 valid responses through email and social media circulation, surpassing the distribution of 118 questionnaires. Direct and moderating effects were tested using PLS-SEM. The results show the significant effects of both FinTech adoption and sustainable practices on financial reporting quality, with sustainable practices having an even more substantial impact. In addition, regulatory compliance and an innovation-friendly culture moderate the relationship between FinTech and financial reporting quality, calculated based on supplementation as acceptable. This model accounts for 20.1% of the variance in the quality of financial reporting. The increase in FinTech adoption is correlated with higher financial reporting. Sustainable practices remain the key to improving the quality of reporting in the body of Jordanian customs clearance. This study benefits Jordan’s policymakers, regulators, and business leaders. Encouraging sustainable practices and a culture of innovation are other steps companies are urged to enhance their financial transparency.